2010
DOI: 10.1056/nejmoa0905606
|View full text |Cite
|
Sign up to set email alerts
|

CISHand Susceptibility to Infectious Diseases

Abstract: Variants of CISH are associated with susceptibility to diseases caused by diverse infectious pathogens, suggesting that negative regulators of cytokine signaling have a role in immunity against various infectious diseases. The overall risk of one of these infectious diseases was increased by at least 18% among persons carrying the variant CISH alleles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 40 publications
1
96
2
Order By: Relevance
“…In recent years there has been a marked increase in our understanding of how SNPs in the human genome contribute to many diseases, including susceptibility to particular infections such as tuberculosis and leprosy (55,56). However, the role that microbial SNPs play in human infection is only beginning to be appreciated (14).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years there has been a marked increase in our understanding of how SNPs in the human genome contribute to many diseases, including susceptibility to particular infections such as tuberculosis and leprosy (55,56). However, the role that microbial SNPs play in human infection is only beginning to be appreciated (14).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Nakajima et al (49) showed that expression of both Cish mRNA and protein is significantly increased in allergen-stimulated CD4 + T cells from hen egg-allergic patients relative to patients not allergic to hen eggs. In addition, Khor et al (50) identified a panel of Cish single nucleotide polymorphisms associated with increased susceptibility to infectious diseases, such as bacteremia, malaria, and tuberculosis. Thus, Cish expression caused by demethylation within the Cish locus in memory T cells may play a role in some infectious and allergic diseases.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Other mechanisms that may contribute to this transient phenotype remain to be determined, and the role of the cish.b paralog awaits further study. Moreover, recent studies have also implicated the human CISH gene as a susceptibility locus for several infectious agents (22), and suggested that CISH contributes to expansion of regulatory T cells in response to microbial infection (66). Therefore, further analysis of the role of CISH in immunity represents an exciting area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…An alternate transgenic mouse model in which CISH was expressed in a T cell-specific manner indicated an independent role in TCR signaling (20). Meanwhile, increased susceptibility to infectious diseases has recently been associated with polymorphisms in the human CISH promoter, which blunted CISH induction following IL-2 stimulation (22).…”
mentioning
confidence: 99%